2019
DOI: 10.3390/toxins11050295
|View full text |Cite
|
Sign up to set email alerts
|

Fengycin Produced by Bacillus amyloliquefaciens FZB42 Inhibits Fusarium graminearum Growth and Mycotoxins Biosynthesis

Abstract: Fusarium graminearum is a notorious pathogen that causes Fusarium head blight (FHB) in cereal crops. It produces secondary metabolites, such as deoxynivalenol, diminishing grain quality and leading to lesser crop yield. Many strategies have been developed to combat this pathogenic fungus; however, considering the lack of resistant cultivars and likelihood of environmental hazards upon using chemical pesticides, efforts have shifted toward the biocontrol of plant diseases, which is a sustainable and eco-friendl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
91
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(99 citation statements)
references
References 41 publications
6
91
0
2
Order By: Relevance
“…DON is one of the most important mycotoxins that causes damage to human and animal health [40]. The results of this study showed that the DON production of F. graminearum strain PH−1 in the GYEP medium was strongly inhibited by the biosynthesized AgNPs at different concentrations.…”
Section: Effect Of Agnps On Don Productionmentioning
confidence: 71%
“…DON is one of the most important mycotoxins that causes damage to human and animal health [40]. The results of this study showed that the DON production of F. graminearum strain PH−1 in the GYEP medium was strongly inhibited by the biosynthesized AgNPs at different concentrations.…”
Section: Effect Of Agnps On Don Productionmentioning
confidence: 71%
“…radicicola [80], F. oxysporum [25,39], F. oxysporum f. sp. spinaciae [27], fumonisin production by F. verticillioides [82] and proliferation of F. graminearum [17,27,80,83,84,85]. On F. graminearum , fengycin causes structural deformations of the hyphae and suppresses in planta proliferation and mycotoxin production [27,84], permeabilization of hyphae [85], and in planta arrest of ear rot development of maize [83].…”
Section: Overview Of Bacillus Species As a Protective Agent Againsmentioning
confidence: 99%
“…Biological control using microorganisms, such as Bacillus spp., Pseudomonas spp., Trichoderma spp., and some plant growth-promoting rhizobacterial strains, has been proposed for the control of diseases caused by soilborne pathogens (Sotoyama, Akutsu, & Nakajima, 2016). Bacillus amyloliquefaciens, a free-living soil bacterium, has obvious antagonistic effects through the secretion of enzymes (chitinase, β-1,3-glucanase) (Arrebola, Sivakumar, & Korsten, 2010), lipopeptides (surfactin, iturin, and fengycin) (Hanif et al, 2019;Ongena & Jacques, 2008), volatile compounds (bacillaene, bacilysin, and difficidin) (Chen, Koumoutsi, Scholz, & Borriss, 2009;Wu, Zhou, Li, & Ma, 2019), and other antifungal substances (Scholz et al, 2011;Wang, Wu, Chen, Lin, & Yang, 2016).…”
Section: Introductionmentioning
confidence: 99%